There Is Not Only Cupressus sempervirens L.: A Review on the Phytochemistry and Bioactivities of the Other Cupressus L. Species - Claudio Frezza; Daniela De Vita; Fabio Sciubba; Chiara Toniolo; Lamberto Tomassini; Marcello Nicoletti; Marco Franceschin; Marcella Guiso; Armandodoriano Bianco; Mauro Serafini; Sebastiano Foddai (Applied Sciences, 2022)
This review article reports for the first time phytochemistry, ethnobotanical uses and pharmacological activities of all Cupressus L. species other than Cupressus sempervirens L. Indeed, the literature survey showed how many other Cupressus species are rich of important phytochemical compounds, widely used in the ethnobotanical field for several purposes and endowed with interesting biological activities, even if they are somehow neglected by the scientific community. This review aims to continue the study of these other Cupressus species and promote more research on them.